CREATING A NEW IMAGINARY FOR LOVE IN RELIGION. Issue 1 (3rd March 2020) - Anderson, Pamela Sue; Fiddes, Paul S.
Abstract: Ideas of love within religion are usually driven by one of two mythologies – either a personal God who commands love or a mystical God of ineffable love – but both are inadequate for motivating love of neighbour. The first tends towards legalism and the second offers no cognitive guidance. The situation is further complicated by there being different understandings of love of neighbour in the various Abrahamic religions, as exemplified in the approaches of two philosophers, Søren Kierkegaard and Emmanuel Levinas. A better approach is therefore to explore actual practices of love in everyday life, and to discover how love might be performed openly and creatively. One such practice is recognition of vulnerability, and this too is often driven by a mythology, in this case one marked by fear, and by a violence either imposed or avoided. One paradigmatic example is the vulnerability felt by speakers, especially women, in front of an audience. A turning from wilful ignorance of vulnerability and a turning to reliance on collective work, modelled on an awareness of mutual vulnerability and openness to the unknown, will help to change our philosophical and social imaginary. The dark myth of vulnerability can be transformed into finding opportunities in vulnerability for openness to affection and so to an enhancement of life. It is only from the perspective of this new imaginary, and from everyday practices of it, that the double love-command – love of God and love of neighbour – will function as any kind of common ground between religions.